Tribological Performance of Si-Doped Hydrogenated Diamond-Like Carbon Coatings in Different Biodiesel. (21st August 2016) - Dorner-Reisel, Annett; Kavaklioglu, Zeynep Burcu; Svoboda, Stefan; Engemann, Jürgen
Abstract : In this paper, two kinds of different biodiesel were tested in terms of their impact on wear resistance of Si-DLC coated 100Cr6 flat worn by an oscillating 100Cr6 ball. The knowledge about the tribological behaviour of different types of biodiesel is rare. Rape and soybean are two of the most common natural sources for biodiesel production. Also, if the quality of biodiesel seems to be similar and, according to the demands, biodiesel from different natural origin could affect changes in the tribological behaviour. Although, soybean methyl ester (SME) gives the best results at room temperature wear tests, 150°C SME reaches wear rates of Si-DLC flat against 100Cr6 ball almost double as high as rapeseed methyl ester (RME). It is evident that, with increasing fraction of oxidation stabilizer C23 H32 O2, the wear rate increases. For silicon doped hydrogenated diamond-like carbon is especially suitable, for use in biodiesels, where certain fraction of humidity, dissociated water, or polar functional groups may present.